Culture and Borderline Personality Disorder in India - Choudhary, Shalini; Gupta, Rashmi (Frontiers in Psychology, 2020)
The present paper discusses how cultural context can be used as an essential tool in the diagnosis of mental disorders as well as in segregating individuals with normal or abnormal personality functioning. Further, such information about the culture can be used to diagnose individuals specifically with borderline personality disorder (BPD). BPD is a mental illness marked by impulsivity and instability in interpersonal relationships, moods, and self-image. We discuss how culture shapes patterns of behavior in the individual with BPD. An extensive review of manifestation of BPD in eastern countries suggests that culture and social norms are the two crucial factors, which can differentiate normal and abnormal behavioral patterns in BPD. For example, the social norms shape and give directions to our interpersonal functioning, emotions are experienced within the cultural context and expressed accordingly, and self is a reflection and representation of one’s culture. Hence, these constructs of BPD (such as interpersonal functioning, emotions, and self) indicate that they are experienced differently in different cultures and vary on the continuum of normal to abnormal personality functioning. The cultural manifestation of BPD helps to understand the specific profile of the three constructs of BPD in an eastern culture like India. A synthesis of studies on prevalence, development, and symptom presentation of BPD in the Indian context is emphasized to support the personality functioning within the constructs of BPD. The literature review indicates that BPD research in India is based only on a few cases and a tiny sample of such patients. However, studies on BPD in the cultural context are minimal and incomprehensive. Hence, it suggests the importance of more empirical studies concerning the appropriate diagnosis of BPD within the cultural context of India.